(untitled) (Revista Científica Compendium, 2023)
The general objective was to describes the financial education programs of Venezuela online banking service under the actor-network theory for the year 2022. It is sought to understand how stakeholders define the problem, propose solutions, implement programs, and try to influence policies and adaptation processes. It is a descriptive, transactional field study under the interpretive approach. A sixteen percent (16%) sample was selected from a population of 31 banks that make up the Venezuelan financial system. The semi-structured interview was used as the data collection technique. Financial education is conceived as a means for financial inclusion and as a complement to an adequate regulatory framework and effective supervision. It is recommended that emphasis be given to understanding of economic and financial information in addition to designing products, services, and programs focused on customer requirements.